2008
DOI: 10.1002/ar.20653
|View full text |Cite
|
Sign up to set email alerts
|

Knee Posture Predicted from Subchondral Apparent Density in the Distal Femur: An Experimental Validation

Abstract: Spatial patterning in the apparent density of subchondral bone can be used to discriminate between species that differ in their joint loading conditions. This study provides an experimental test of two hypotheses that relate aspects of subchondral apparent density patterns to joint loading conditions. First, the region of maximum subchondral apparent density (RMD) will correspond to differences in joint posture at the time of peak locomotor loads; and second, differences in maximum density between individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 91 publications
4
48
0
Order By: Relevance
“…1, inset point C) and the anterior extent of the RMD (Fig. 1, inset point E), as this angle (θ) most closely matched kinematically measured joint angles in the experimental study of Polk et al (2008). We exported coordinate measurements from tpsdig2 and calculated angles using the law of cosines.…”
Section: Methodsmentioning
confidence: 91%
See 4 more Smart Citations
“…1, inset point C) and the anterior extent of the RMD (Fig. 1, inset point E), as this angle (θ) most closely matched kinematically measured joint angles in the experimental study of Polk et al (2008). We exported coordinate measurements from tpsdig2 and calculated angles using the law of cosines.…”
Section: Methodsmentioning
confidence: 91%
“…These researchers used differences in substrate orientation to alter the locomotor postures of 2 groups of sheep during twice-daily bouts of exercise for a period of 45 d. They obtained kinematic measurements for the knee postures during locomotion and compared these measurements to joint posture estimates obtained from bone apparent density patterns. They found that the position of the region of maximum subchondral bone apparent density could be used to reconstruct joint postures that closely matched kinematically measured joint postures (Polk et al 2008). Further, because this study did not find differences in peak apparent density magnitudes between the experimental groups, they inferred that the observed patterns of apparent density resulted from the differences in habitual loading conditions instead of differences in loading magnitude.…”
Section: Background To Analyses Of Subchondral Bone Apparent Densitymentioning
confidence: 92%
See 3 more Smart Citations